Stress transfer from opening hydraulic fractures controls the distribution of induced seismicity - Kettlety, T; Verdon, JP; Werner, MJ; Kendall, JM (American Geophysical Union, 2019)
Understanding the dominant physical processes that cause fault reactivation due to fluid injection is vital to develop strategies to avoid and mitigate injection-induced seismicity. Injection-induced seismicity is a risk for several industries, including hydraulic fracturing, geothermal stimulation, oilfield waste disposal and carbon capture and storage, with hydraulic fracturing having been associated with some of the highest magnitude induced earthquakes (M > 5). As such, strict regulatory schemes have been implemented globally to limit the felt seismicity associated with operations. In the UK, a very strict “traffic light” system is currently in place. These procedures were employed several times during injection at the PNR-1z well at Preston New Road, Lancashire, UK, from October to December 2018. As injection proceeded, it became apparent to the operator that stages were interacting with a seismogenic planar structure, interpreted as a fault zone, with several ML > 0.5 events occurring. Microseismicity was clustered along this planar structure in a fashion that could not readily be explained through pore pressure diffusion or hydraulic fracture growth. Instead, we investigate the role of static elastic stress transfer created by the tensile opening of hydraulic fractures. We find that the spatial distributions of microseismicity are strongly correlated with areas that receive positive Mohr-Coulomb stress changes from the tensile fracture opening, while areas that receive negative Mohr-Coulomb stress change are quiescent. We conclude that the stressing due to tensile hydraulic fracture opening plays a significant role in controlling the spatiotemporal distribution of induced seismicity.